2021
DOI: 10.1016/j.immuni.2021.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Metformin inhibition of mitochondrial ATP and DNA synthesis abrogates NLRP3 inflammasome activation and pulmonary inflammation

Abstract: Acute respiratory distress syndrome (ARDS), an inflammatory condition with high mortality rates, is common in severe COVID-19, whose risk is reduced by metformin rather than other anti-diabetic medications. Detecting of inflammasome assembly in post-mortem COVID-19 lungs, we asked whether and how metformin inhibits inflammasome activation while exerting its anti-inflammatory effect. We show that metformin inhibited NLRP3 inflammasome activation and interleukin (IL)-1β production in cultured and alveolar macrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
155
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(184 citation statements)
references
References 96 publications
8
155
1
Order By: Relevance
“…The diabetes drug metformin indirectly inhibits NLRP3 by regulating mTOR, and its use is significantly associated with reduced mortality among patients with COVID-19 and type 2 diabetes. Metformin was also recently shown to inhibit NLRP3 activation and lung inflammation in SARS-CoV-2-infected mice 164 , 165 .…”
Section: Clinical Interventionsmentioning
confidence: 99%
“…The diabetes drug metformin indirectly inhibits NLRP3 by regulating mTOR, and its use is significantly associated with reduced mortality among patients with COVID-19 and type 2 diabetes. Metformin was also recently shown to inhibit NLRP3 activation and lung inflammation in SARS-CoV-2-infected mice 164 , 165 .…”
Section: Clinical Interventionsmentioning
confidence: 99%
“…Our study is limited to a single in vitro measure of metformin as a therapeutic for COVID-19, so a great deal of further study is necessary in order to establish this drug as a viable treatment. To this end, one recent study demonstrated metformin as efficacious in preventing acute respiratory distress syndrome in a preclinical animal model of COVID-19 ( 97 ). Therefore, although metformin is most likely to be useful as an adjuvant rather than front-line therapy for severe acute COVID-19, it remains an attractive option for targeting hyperinflammation in this disease to limit severity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Xian et al demonstrated in mouse models, the anti-inflammatory role of metformin via inhibition of the NLRP3 inflammasome and interlekin-1β induced acute respiratory distress syndrome in SARS-CoV-2 infection. [30] Similarly statins such as simvastatin and lovastatin were found to be most effective in severe SARS-CoV-2 infection exerting its influence via cytotoxic T lymphocytes and regulatory T cell induction. [31] As the literature assessing the effect of medications targeting dysglycemia, hypertension, thrombosis, [32] and hypercholesterolemia on SARS-CoV-2 infection and severity tends to suggest modest protection against infection and mortality, future studies will be enhanced by accounting for medications to avoid negative confounding towards the null (eg, weaker associations due to the protective effect of medications being more common among patients with vs. without diabetes).…”
Section: Confoundingmentioning
confidence: 99%